An Energy Constraint Approach to Improve Lifetime and Reduce Routing Overhead in Heterogeneous MANET - . Poonam; Hirdesh Kumar; Santar Pal Singh (Journal of ICT Research and Applications, 2019)
Heterogeneous Mobile Ad-hoc Networks (H-MANET) contain different configuration nodes, each of which communicates over a wireless channel and is capable of movement. Heterogeneous wireless networking has attracted lot of interest from consumers in the previous few years for its applications in mobile and personal communications. One of the main constraints in MANET is the high probability of failure due to energy-exhausted nodes. So if the path selected for communication has low battery life then the path breaks prematurely and the re-discovery phase starts, which costs more overhead in the network. Therefore, there is unequal consumption of node energy, which must be prevented. The energy expenditure of the nodes should be balanced in order to minimize path breakage. This can be done by finding the communication path that is the most energy-efficient among alternative disjoint paths. This approach reduces path breakage and routing overhead caused by nodes with low battery life dying in the communication path, thus increasing the network's lifetime.